The Role of Leadership on Corporate Social Responsibility Strategies in Lithuanian National Context: Case Study Mars Lithuania - Nosirevaite, Evelina Jelena (2010)
The main objective of this paper is to look at Lithuania’s national context and CSR development there. Furthermore, after conducting a research on leadership theory, leadership style is found that is most effective with CSR strategies. Also, the purpose is to further identify the role of leadership for successfully generating CSR in Lithuania and possible barriers for CSR implementation in Lithuania. The research starts with the history of Lithuania, from its beginning to the gaining independence and entering the European Union. Although by the late 1990s Lithuania had become favourable in the eyes of investors, with government passing laws, excellent Lithuanian infrastructure and low labour cost; however, the changing political environment has eventually created uncertainty and difficulty for business to adjust to common changes in regulations in Lithuania. Other externalities that transition period has brought was the weakened civil society and it created a culture of political passiveness and distrust, especially people’s distrust in politics. The dominant culture of distrust is further facilitated by the negative information that the media provides. Since Lithuania’s entrance into EU, the country has been facing a challenge to respond and adopt global environmental and social integration. One of the ways that Lithuanian private sector could better integrate into EU market is to create an enabling environment for CSR. Although the barriers for CSR development in Lithuania exist, United Nations Development Programme together with the Ministry of Social Security and Labour in Lithuania are actively facilitating the environment that would enable CSR growth in Lithuania. One of the institutional drivers for CSR is the individual or leader within organisation (Angus-Leppan et al., 2010). After conducting a literature review on leadership, it became evident that despite many different definitions and styles of leadership, the most mentioned and discussed in academic literature were used in this paper. The most effective leadership style that shapes organisational values and motivates its followers to act beyond organisational expectation is transformational leadership (Rubin et al., 2005, in Osborn and Marion, 2009; Simola et al., 2010; Yammarino et al., 1993). This type of leadership appeals to moral values and the outcomes of such leadership are changes in organisation’s culture and strategies (Carlson and Perrewe, 1995). Considering the Lithuanian developing country context, where CSR is implicit or underdeveloped, transformational leadership was found to be linked in this context (Angus-Leppan et al., 2010) and thus this type of leadership will be applied when conducting a case study in the chosen organisation. The organisation that was chosen is Mars Lithuania, which is a multinational company successfully operating in Lithuania. After conducting interviews with the management of the organisation, transformational leadership style was identified and its role on CSR strategies. The strong role of leadership was identified outside the Mars organisation as well, where the company and its employees contribute to community and environment.